5(3-r)+2=3(r+2)

Simple and best practice solution for 5(3-r)+2=3(r+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3-r)+2=3(r+2) equation:


Simplifying
5(3 + -1r) + 2 = 3(r + 2)
(3 * 5 + -1r * 5) + 2 = 3(r + 2)
(15 + -5r) + 2 = 3(r + 2)

Reorder the terms:
15 + 2 + -5r = 3(r + 2)

Combine like terms: 15 + 2 = 17
17 + -5r = 3(r + 2)

Reorder the terms:
17 + -5r = 3(2 + r)
17 + -5r = (2 * 3 + r * 3)
17 + -5r = (6 + 3r)

Solving
17 + -5r = 6 + 3r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-3r' to each side of the equation.
17 + -5r + -3r = 6 + 3r + -3r

Combine like terms: -5r + -3r = -8r
17 + -8r = 6 + 3r + -3r

Combine like terms: 3r + -3r = 0
17 + -8r = 6 + 0
17 + -8r = 6

Add '-17' to each side of the equation.
17 + -17 + -8r = 6 + -17

Combine like terms: 17 + -17 = 0
0 + -8r = 6 + -17
-8r = 6 + -17

Combine like terms: 6 + -17 = -11
-8r = -11

Divide each side by '-8'.
r = 1.375

Simplifying
r = 1.375

See similar equations:

| -4x+21=3x | | -7x+4=2x-5 | | -8x-1=x+26 | | -4x-9=x+1 | | -3w+5=7w-3 | | 12x^4-4x^2-5=0 | | -3x+8=x-4 | | 2a+17=6a+5 | | -3u+10=5u+3 | | 5x+1=12-x | | 5p+1=3p+13 | | 5=z+7 | | 5=z-1 | | 5=z-12 | | -0.25*x^2+1.25*x+1=0 | | -0.25*x^2+1.25*x-1=0 | | 0.25*x^2+1.25*x+1=0 | | -×=-3/4 | | h=-16t^2+224t | | 0.25*x^2+1.25*x-1=0 | | 7(1-x)/10=1 | | 3+(5+a)=(3+5)+a | | 2x(24/3)-2= | | 174/36 | | x^3+15x^2=x^2-49x | | 2x^4-14x^3-60x^2=0 | | 10x+6x=48 | | 120(x/100)=1 | | 70(1-x)/100=1 | | 7(1-x)=1 | | 5/6x-3x=23 | | 7/2x-5/6x=1 |

Equations solver categories